(untitled) (Tecnología y Sociedad, 2020)
Because of its task-dependent character, the “Deficit Model”, which conceives public communication of science and technology as a “correction process” of supposed ignorance, disinterest or rejection from society to science and technology, may be episthemologically approached by philosophy of technology, especially by some tools developed by Andrew Feenberg and by Gilbert Simondon for critical analysis of relationships between knowledge and power inside of technical systems. Such analysis reveals that a radical criticism of biases and assymetrical relationships established between scientific-technological systems and the people neither determines nor presuposes, at all –but doesn’t unable it–, any questioning of intrinsic values of scientific and technological knowledge at its specifity.